The study of CPF : is it aiming for too much and can it still serve its original objective in view of developments and changes made to it. - Lian, Jason Wei Keong. (2008)
The objective of this paper is to conduct a study on the developments and changes of the Central Provident Fund system, then determining whether is it aiming for too much, and can it still achieve its original objective of providing for retirement. Since its inception in 1955, the scope of the system has been expanded beyond covering the original objective of providing for retirement needs. With the latest inclusion of a CPF annuity plan, we ascertain whether the developments and changes introduced would detract the CPF from its original objective. Using secondary data, we analyze the major developments and changes made to the CPF. Our analysis found that the most of the developments made to the CPF have not diluted its main objective of providing a retirement nest and served as an enhancement to the CPF system with the exception of the CPF Investment Scheme where CPF savings were lost through purchases of approved financial instruments. We also established that changes to the employers’ contribution rates and the CPF interest rates to-date have provided protection to members’ retirement savings. In future, the government must deliberate on decisions to further expand the scope of the CPF to ensure the CPF had kept its objective of providing a retirement nest in sight. A similar analysis could be carried out as fresh developments and changes are made to the CPF in future.